What factors influence the abundance and distribution of sacred forests in Odisha, a densely forested state in eastern India?. Issue 4 (4th July 2018) - Rath, Subhani; John, Robert
Abstract: This is a report on sacred forests of Odisha, a large and densely forested state in eastern India. Using district-level data from government agencies on geographical area, demographics, forest cover, and sacred forest sizes and numbers, we test what factors influence the observed distributions and abundance of sacred forests. Results show that at the district level, population size of scheduled tribes was unrelated to total population size. Forest area was greater in larger districts, and where tribal populations were greater, but per cent forest cover declined with overall population density. There are 2166 documented sacred forests in the state of Odisha, with most being small (median = 0.2 ha). Multiple regression analyses show that the number of sacred forests is unrelated to total forest area but is significantly positively associated with Tribal population size. Sacred forests have survived decline during recent deforestation, and indigenous cultural practices appear to promote the persistence of natural vegetation.